2022
DOI: 10.3325/cmj.2022.63.273
|View full text |Cite
|
Sign up to set email alerts
|

Croatian genetic heritage: an updated Y-chromosome story

Abstract: AimTo analyze an additional set of ˝Y-chromosome genetic markers to acquire a more detailed insight into the diversity of the Croatian population.Methods A total of 518 Yfiler Plus profiles were genotyped. Allele frequencies, haplotype frequencies, and haplotype diversity were calculated by using the STRAF software v. 2.0.4. Genetic distances were quantified by Rst with AMO-VA online tool from the YHRD. The evolutionary history was inferred with the neighbor-joining method of phylogenetic tree construction in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…7; Tables S16-S17). This ancestry contribution is two to three times higher than the frequency of South-Slavic-associated Y-chromosome haplogroups (R1a-M417, I2a-M423) (67,68) in the modern Albanian population (15% combined; Fig. S8), suggesting that Slavic-related admixture may have been largely female-mediated, as has been shown in 10 th century Serbia (3).…”
Section: The Formation Of the Modern Albanian Genomementioning
confidence: 68%
See 1 more Smart Citation
“…7; Tables S16-S17). This ancestry contribution is two to three times higher than the frequency of South-Slavic-associated Y-chromosome haplogroups (R1a-M417, I2a-M423) (67,68) in the modern Albanian population (15% combined; Fig. S8), suggesting that Slavic-related admixture may have been largely female-mediated, as has been shown in 10 th century Serbia (3).…”
Section: The Formation Of the Modern Albanian Genomementioning
confidence: 68%
“…We argue that based on insights from the PCA and their uniparental markers, these outlying individuals likely date to post-Medieval times. Individuals I18721 and I18719 are assigned to haplogroup I2-M423>I-Y3120 (Table S23), which is associated with the Slavic expansion toward southern Europe during the Migration Period, and has experienced major founder effects in the South Slavic population of the Balkans (48,68,82). This haplogroup is extremely unlikely to have entered the Western Balkans in the Bronze Age, as our extensive haplogroup dataset shows that subclades downstream of I2-M423 appear in the region primarily during the Migration Period (Fig.…”
Section: Datasetmentioning
confidence: 99%
“…A considerable number of population-genetic studies have, in the last few decades, provided a large amount of Croatian and other SEE population data based on Y-chromosome markers. The data reflect the turbulent and complex demographic history of this region, influenced by gene flow from various parts of Eurasia and a long history of intermixing [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. Studies have confirmed a high level of Y-haplogroup and -haplotype diversity in SEE, with three NRY haplogroups accounting for the majority of paternal genetic variation—namely the I2a, R1a, and E1b clades [ 38 , 39 ].…”
Section: Modern Y-chromosome Diversity Of Southeastern Europementioning
confidence: 83%
“…Among these, short tandem repetitions (STRs) are relevant in genetic studies of populations. They have an average frequency of mutation of about 0.2% per generation [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Y-STR haplotype represents the set of alleles on the same chromosome. At the same time, major haplogroups (branches of the Y chromosome phylogeny) reflect the establishment and expansion of major population groups and can provide information about the time scale and route of major migration events [ 1 ].…”
Section: Introductionmentioning
confidence: 99%